Cellular Stress Promotes Cellular Suicide: Review Article - Hiyam Maty (Journal of Applied Veterinary Sciences, 2023)
The focus of this overview was to elucidate the different kinds of stresses that influence cell survival, growth, and cellular functions, in addition to cellular quiescence and cellular suicide, as well as how the cell tries to respond to these stressful stimuli. A cell's cycle is a sequence of developments that enables a cell to replicate every component of itself, divide into two nearly identical new cells, and endow each with the information and resources it needs to repeat the process. For tissue homeostasis, the ideal stabilization of proliferation of cells, demise of cells, and the proportion of positive to negative signals determines if the cell is alive or dead. Cells could indeed cope with adverse conditions in an assortment of ways, from triggering long-term survival strategies to establishing the demise of cells, which ultimately expel dead cells. The kind, intensity, and time frame of the stress, plus the kind of cell, all play a significant role in determining whether cells mount a defensive or destructive response to stress. This review will talk about the consequences of cellular responses to stress and discuss a range of stressful situations and the degree to which the animal's cells' react to multiple exhausting factors ranging from the physiologically programmed advancement of cells to cellular senescence and/or a variety of pathological disorders.